Calculation of the total kinetic energy distributions for neutron fission of plutonium isotopes - M. Jamiati (مجله علوم و فنون هسته‌ای, 2022)
In the present study, the total kinetic energy (TKE) values of neutron fission fragments of plutonium isotopes were calculated using the scission point model. The deformation parameters were obtained for neutron fission of plutonium 239, 241, and 242 by comparing the calculated results with experiments in the scission point model. TKE values were evaluated for neutron fission of other plutonium isotopes with these deformation parameters. Using the results of the fission deformation parameters, the average kinetic energy of all neutron fission fragments for the rest of the plutonium isotopes is calculated. The maximum average kinetic energy of all neutron fission fragments for plutonium isotopes is 185 MeV.